A Quantum Circuit for Three Quantum Bits to Produce Quantum Entanglement States (ML- Quadripartite). - Saleh, Mezher B; George, Loay E (Al-Nahrain Journal of Science, 2018)
In this research, a quantum system consists of three qubits is considered; it has eight states (ǀ000˃, ǀ001˃, ǀ010˃, ǀ011˃, ǀ100˃, ǀ101˃, ǀ110˃ and ǀ111˃). Each of these states is passed through a quantum circuit made of a sequence of quantum gates. The circuit applies X- gate on the first qubit from the left, then using CNOT-gate on the first and second qubits and using the Hadamard-gate on the first qubit. Finally, Hadamard–gate is applied on the third qubit. When the state ǀ000˃ is passed as input through the proposed quantum circuit then the output includes four entanglement states; for the other input states the output will be another non-repeatable entanglement states. So, for using all states in quantum circuit the result will be eight equations each one consists of four entanglement states; which called ML- Quadripartite.